Error variance bias in neighbour balance and evenness of distribution designs. (3rd November 2019) - Williams, E. R.; Piepho, H. P.
Summary: Neighbour balance and evenness of distribution designs help to address user concerns in the two‐dimensional layout of agricultural field trials. This is done by minimising the occurrence of pairwise treatment plot neighbours and ensuring that the replications of treatments are spread out across rows and columns of a trial. Such considerations result in a restriction on the normal randomisation process for a row‐column design which can lead to error variance bias. In this paper, uniformity trial data is used to assess the degree of this bias for both resolvable and non‐resolvable designs. Comparisons are made with a similar investigation using Linear Variance spatial designs. Abstract : This article assesses the degree of error variance bias associated with neighbour balance and evenness of distribution designs.